PENENTUAN INDEKS BIAS DARI KONSENTRASI SUKROSA (C12H22O11) PADA BEBERAPA SARI BUAH MENGGUNAKAN PORTABLE BRIXMETER - Tiffany Rahma Novestiana; Eko Hidayanto (Youngster Physics Journal, 2015)
One of the determination of the quality of the juice is concentration. Concentration can determine the value of the refractive index with a refractive index with a Abbe Refractometer. This experiment was determined the value of the refractive index of branded fruit juices using Portable Brixmeter was to get correlation between refractive index and concentration and correlation between concentration and length of measurement, and quality of fruit juice using Portable Brixmeter. The research was conducted by dilution and observation of length time measurement of fruit juice concentration. Data were analized by approach linier charts for dilution, while the length of time measurement of juice concentration with quadratic approach of polynomial. The amount of sucrose liquid concentration is comparable with its refractive index. Correlation between liquid concentration of C sucrose with refractive index n in pure sucrose (ns):0,0018C+ 1,3270 for fruit juice of guava, orange, apple, and soursop respectively (nja):0,0013C+1,3336; (nje):0,0014C+1,3334; (na):0,0015C+1,3329 and (nsi):0,0014C+1,3331. According to the length measurement of the concentration, the longer of time measurement decreased the concentration value. Concentration equation contained fruit juice taste guava, orange, apple, and soursop respectively: (Cja):-0.0016t2+0.0199t+13.365; (Cje):- 0.0062t2+0.0916t+11.444; (Ca):-0.0024t2-0.0016t+12.472 and  (Csi):-0.0032t2+0.0015t+12.158. Keywords: refractive index, sucrose concentration, portable brixmeter, fruit juice.